2016
DOI: 10.7729/83.1127
|View full text |Cite
|
Sign up to set email alerts
|

Flipping the Counseling Classroom to Enhance Application-Based Learning Activities

Abstract: Flipped learning is an instructional approach that employs asynchronous video lectures as homework and active, group-based activities in the classroom (Bishop, 2013). During the past decade, this teaching approach has increased in popularity among K-12 teachers and higher education instructors. Though one model of flipped learning is traditionally described in the literature, several models exist and are detailed in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 24 publications
1
21
0
2
Order By: Relevance
“…Lage et al found the majority of students responded positively to the inverted class. Researchers credit current interest in flipped learning to Jonathan Bergmann and Aaron Sams, two high school chemistry teachers who in 2006 began assigning video lectures to students before class and facilitating hands‐on lab activities in class (Bergmann & Sams, 2012; Merlin, 2016a; Moran & Milsom, 2015). Since then, educators across school levels have become interested in flipped learning as a method to improve student learning (Moran & Milsom, 2015).…”
Section: Flipped Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…Lage et al found the majority of students responded positively to the inverted class. Researchers credit current interest in flipped learning to Jonathan Bergmann and Aaron Sams, two high school chemistry teachers who in 2006 began assigning video lectures to students before class and facilitating hands‐on lab activities in class (Bergmann & Sams, 2012; Merlin, 2016a; Moran & Milsom, 2015). Since then, educators across school levels have become interested in flipped learning as a method to improve student learning (Moran & Milsom, 2015).…”
Section: Flipped Learningmentioning
confidence: 99%
“…Using predominantly quantitative means, researchers have examined several flipped learning variables, including student performance, student and educator perceptions, and learning environments across a range of disciplines, such as engineering, medicine, and information technology (Davies, Dean, & Ball, 2013; Mason, Shuman, & Cook, 2013; Prober & Heath, 2012). In a review of 24 quantitative studies on flipped learning across fields, Bishop and Verleger (2013) concluded that students’ perceptions of flipped classrooms were consistently positive with a few students regularly dissenting (Blair et al, 2016; Merlin, 2016a).…”
Section: Flipped Learningmentioning
confidence: 99%
See 3 more Smart Citations